2010
DOI: 10.1364/ol.36.000052
|View full text |Cite
|
Sign up to set email alerts
|

Waveguide-integrated telecom-wavelength photodiode in deposited silicon

Abstract: We demonstrate photodiodes in deposited polycrystalline silicon at 1550 nm wavelength with 0.15 A/W responsivity, 40 nA dark current, and gigahertz time response. Subband absorption is mediated by defects that are naturally present in the polycrystalline material structure. The material exhibits a moderate absorption coefficient of 6 dB/cm, which allows the same microring resonator device to act as both a demultiplexing filter and a photodetector. We discuss the use of deposited silicon-based complementary met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 15 publications
1
43
1
Order By: Relevance
“…Sub-band gap detection by means of deliberately created defects from silicon implantation [14] or relying on surface states [15] presents a solution. Another option is again introducing a material with the desired properties as done with germanium [16] or using polycrystalline silicon [17]. An organic material for high-speed detection at IR wavelengths remains to be found.…”
Section: Detectorsmentioning
confidence: 99%
“…Sub-band gap detection by means of deliberately created defects from silicon implantation [14] or relying on surface states [15] presents a solution. Another option is again introducing a material with the desired properties as done with germanium [16] or using polycrystalline silicon [17]. An organic material for high-speed detection at IR wavelengths remains to be found.…”
Section: Detectorsmentioning
confidence: 99%
“…The effective free-carrier recombination time has been demonstrated to be τ Carrier ≈ 100 ps [Preston et al 2009], or approximately four times faster than comparable devices in crystalline silicon. Additionally, it has been shown the polycrystalline silicon can be used as a moderately absorbing material for photodetectors [Preston et al 2011].…”
Section: Materials For Silicon Photonicsmentioning
confidence: 99%
“…Recent efforts have enhanced linear absorption by implanting ions to create defects [Bradley et al 2005], obtaining bandwidths exceeding 35GHz and responsivities as high as 10A/W in different devices [Geis et al 2009]. Similarly, deposited polycrystalline silicon can be used as the absorbing material in a microring resonator geometry to enhance absorption and reduce the footprint, demonstrating responsivities as high as 0.15A/W [Preston et al 2011]. Due to the moderate optical absorption, the absorbing polycrystalline silicon material can serve as both the demultiplexing filter and the photodetector.…”
Section: Switchesmentioning
confidence: 99%
“…The high-speed performance of waveguide integrated detectors has been previously investigated by Geis et al,5 where the potential of this technology was demonstrated for use as a high-speed receiver diode. Silicon defect detectors have recently been incorporated into ring resonator structures based on ion-implanted silicon, 6,7 deposited silicon 8 and surface state defects. 9 The resonator geometry provides a compact device footprint, wavelength selectivity, and increased responsivity due to the buildup of optical intensity within the cavity.…”
Section: Introductionmentioning
confidence: 99%